Autosomal dominant chronic mucocutaneous candidiasis with STAT1 mutation can be associated with chronic active hepatitis: A case report - Liu, Lingling; Huang, Yuan; Liao, Yi; Shu, Sainan (Frontiers in Pediatrics, 2023)
Background: Chronic mucocutaneous candidiasis is a heterogeneous primary immunodeficiency disease characterized by chronic or recurrent skin, nail and mucosal Candida infection. Mostly related to STAT1 acquired function (GOF) mutation (GOF-STAT1 mutation). Case presentation: we present 2-year-old girl with recurrent liver dysfunction, oral candidiasis, acute bronchial pneumonia, and cytomegalovirus infection. After a series of treatments (the antifungal voriconazole, nystatin treatment for oral Candida, antibiotics against bacterial infection, protection of the liver with bicyclol) the child still exhibited liver splenomegaly. We did not find the cause through routine hospital tests. We speculated whether the child had combined immunodeficiency. So we did High-precision clinical display PLUS detection. The result revealed a heterozygous GOF mutation (p.R274W) in the coiled-coil domain of the transcription factor STAT1. Conclusion: The clinical manifestations of CMCD caused by GOF-STAT1 mutations are complex and range from mild local fungal infections to severe systemic diseases, even life-threatening. For children with repeated fungal infections, clinicians should be aware of the possibility of this disease, because active treatment can save the lives of these patients.